Estrategias pedagógicas alternativas para el desarrollo de habilidades cognitivas en niños de 4 a 5 años - Pilatásig Ayala, María Marina (2022)
This degree work addressed the problem of the limited use of alternative pedagogical strategies for the development of cognitive skills in children aged 4 to 5 years. With the objective of strengthening the development of cognitive abilities of children 4 to 5 years of initial education 2 of the Educational Unit "Pastocalle" through a guide of alternative pedagogical strategies. For this, a methodology framed in the interpretive paradigm was used, in the qualitative approach, through the design of action research and the application of interview, focus group and observation techniques. With this, the result has been obtained, firstly, a low level of knowledge and use of alternative pedagogical strategies by teachers to favor the development of cognitive skills in early childhood, and, secondly, the difficulties in the development of the skills of perception, attention and memory presented by children aged 4 to 5 years. For this reason, a guide of alternative pedagogical strategies based on gamification and educational games was designed to enhance the development of perception, attention and memory in infants, skills that are essential for learning throughout life. . The validity and feasibility of the proposed proposal has been supported by the evaluative judgment of four experts and four users, who have given their support to the relevance of the contents of the proposal and its usefulness to strengthen the development of cognitive skills in Early Childhood Education.